Main Datasets of the 2020 Update of the European Seismic Hazard Model (ESHM20) ... : ESHM20 - EFEHR Input data ... - Danciu, Laurentiu; Nandan, Shyam; Reyes, Celso; Basili, Roberto; Weatherill, Graeme; Beauval, Céline; Rovida, Andrea; Vilanova, Susana; Sesetyan, Karin; Bard, Pierre-Yves; Cotton, Fabrice; Wiemer, Stefan; et al. (EFEHR European Facilities of Earthquake Hazard and Risk, 2021)
This folder contains the main components of the ESHM20. Data format is ESRI shapefiles, and the main attributes are described in Appendix A of the ESHM20 report (Danciu et al 2021): - unified earthquake catalog - the completeness zones (used to determine the magnitude of completeness M c ) - tectonic source zones for the shallow crust model - area source zones for the shallow crust model - shallow crust fault model - subduction source models - smoothed seismicity model - polygons that define regions used to split the smoothed seismicity grid for the calculations. - buffer that surrounds the fault models, used to determine which smoothed-seismicity grid-points are impacted by each fault - tectonic source zones for the deep model - area source zones for the deep model - area source zones for the shallow volcanic model - tectonic source zones for the Iceland model - area source zones for the Iceland model ...